Analysis of Innovative Development for the Use of (Guadua angustifolia Kunth) in the Substitution of Illicit Crops (2020)
With the signing of the 2016 peace agreements, one of the problems that manifests itself is the considerable increase in illicit crops, especially in Colombian border areas such as Cauca, Nariño and Norte de Santander. Taking into account the implementation strategy of the agreements regarding the substitution of illicit crops and comprehensive rural reform, this work presents an alternative proposal for the comprehensive and sustainable implementation of the cultivation of (Guadua angustifolia, Kunth) and the opportunity for innovation. that guadua has for the production of materials with added value, offering an opportunity to improve the quality of life for the Colombian Pacific. A documentary review is made related to the realities and challenges posed by the implementation of the peace agreements, it is established that the cultivation and use of guadua is a viable and sustainable strategy for the voluntary eradication of coca crops aimed at the territorial development of Tumaco, Nariño applying a strategy based on four fundamental axes: 1) Community participation 2) Study, socialization and implementation of the cultivation of guadua as a replacement strategy 3) Industrial development of guadua products, 4) Accompaniment of the security forces and the National Police and 4) Monitoring and permanent assistance from the State.